CHATGPT’S POTENTIAL IN ACADEMIA AND BEYOND: AN EMPIRICAL EXAMINATION (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This paper presents a thorough investigation  into the multifaceted impact of ChatGPT  on academia and research, with emphasis on  revolutionizing these domains through the  integration of AI models. The primary objective  is to develop a comprehensive survey instrument  to capture various parameters and nuances  associated with the influence of ChatGPT.  The study engages in a thorough exploration  of participants’ perspectives, examining factors  such as perceived usefulness, willingness to  explore innovative applications, and beliefs  about the potential role of AI models in shaping  academic research and publication. Ethical  considerations, bias mitigation strategies, and  user satisfaction are also integral components of  the study.
Keywords: ChatGPT; Academia; Research Impact; AI Integration; Survey Instrument